2020
DOI: 10.4322/pmd.2019.019
|View full text |Cite
|
Sign up to set email alerts
|

Corporate engagements with startups: antecedents, models, and open questions for innovation management

Abstract: Corporate Engagements with Startups (CEwS) are Open Innovation initiatives in which large established companies interact with startups aiming at improving innovation performance. Complementary characteristics of established companies (e.g. resource availability, inertia…) and startups (resource scarcity, flexibility, technologies…) are starting points for such engagements. However, large companies and startups are remarkably different so that working together can be overly challenging. Especially for large com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
15
0
4
Order By: Relevance
“…the contract signing that precedes the project execution, following Plewa et al. (2013) – contributing to reducing disparities in project scope and assignments, which is likely to impact bureaucratic work (Bagno, Salerno, Souza Junior, & O'Connor, 2020). In doing so, research trends and market needs are the predominant topics of the initial discussion, instead of an abrupt immersion in topics like intellectual property rights and financial division of royalties, for instance. A shared work environment provides mutual benefits other than those associated with R&D outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the contract signing that precedes the project execution, following Plewa et al. (2013) – contributing to reducing disparities in project scope and assignments, which is likely to impact bureaucratic work (Bagno, Salerno, Souza Junior, & O'Connor, 2020). In doing so, research trends and market needs are the predominant topics of the initial discussion, instead of an abrupt immersion in topics like intellectual property rights and financial division of royalties, for instance. A shared work environment provides mutual benefits other than those associated with R&D outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…The proposition of a methodology to build an initial R&D portfolio contributes to “unfuzzying” the FFE of a company’s innovation process (Bagno, Salerno et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, Cajuela and Galina (2020) found that startups are influenced by the organizational culture of large corporations, especially those that encourage cross-functional thinking. On the other hand, established companies that work together with startups have the chance to foster a culture for innovation (BAGNO et al, 2020).…”
Section: Critical Factors In the Collaboration Between Startups And E...mentioning
confidence: 99%
“…Corporate incubation programs also allow startups to develop specific capabilities to absorb knowledge through mentorship networks and specialized training (CAJUELA; GALINA, 2020). However, one of the great challenges of corporate acceleration programs is the institutionalization of knowledge (BAGNO et al, 2020). Most of these programs take place outside organizational structures, which Renata Simões Guimarães e Borges, Gilvan Augusto Silva can compromise the integration and consolidation of technology or knowledge generated within the program.…”
Section: Critical Factors Of Incubation Programsmentioning
confidence: 99%
See 1 more Smart Citation